Traditional games: Improving manners through carom - 'Ilmi, Achmad Miftachul; Santoso, Djoko Budi; Muslihati, Muslihati (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
In the era of the industrial revolution 4.0, there was a decline in the character of the Indonesian nation, such as manners and less commendable individual behaviour. Hence, the importance of strategies for enhancing and developing individual manners. The purpose of this research is to produce a guidebook and play media of Si-KARTUN to develop the manners of junior high school students. The research and development method used was adapted from the Borg & Gall model. The research and development subjects consist of two media experts, one material expert, and two potential users (mentors). Expert and prospective user test tools use a product acceptance scale based on aspects of accuracy, function, interest, and accuracy in providing group guidance services to foster the behaviour of junior high school students. Data analysis of material experts and candidates used the inter-rater agreement model while the results of the media evaluation were analyzed on an average basis. Based on the evaluation results of experts and potential users, Si-KARTUN meets the appropriate criteria, is practical, attractive, and easy to use; Therefore, the Si-KARTUN product is feasible to be applied. By using the Si-KARTUN product, the guidance process is much more fun and interesting.